A Meta‐Analysis of Environmentally Sustainable Supply Chain Management Practices and Firm Performance. Issue 2 (16th April 2013) - Golicic, Susan L.; Smith, Carlo D.
<x xml:space="preserve">Abstract</x> Studies linking environmental sustainability to firm performance have been increasing as more companies are contemplating the implementation of sustainable practices internally and in coordination with other firms along their supply chains. However, findings from these studies have found positive and negative associations, leaving practitioners perplexed as to what actions would be beneficial to pursue. With hypotheses grounded in the natural resource–based view of the firm, the current study examines over 20 years of research on environmental supply chain practices using a meta‐analysis to determine whether the overall effect of these specific practices on firm performance is, in fact, positive. The results show that the link between environmental supply chain practices and market‐based, operational‐based and accounting‐based forms of firm performance is positive and significant, providing support for the business case that sustainable supply chain management results in increased firm performance. Different operationalizations of supply chain practices — upstream, design, production and downstream — along with industry, sample region, firm size and time are examined as moderators of this relationship with nuanced results that help to extend the discipline's understanding of the relationship between environmentally sustainable supply chain management and firm performance.